A novel approach for the biosynthesis of silver oxide nanoparticles using aqueous leaf extract of Callistemon lanceolatus (Myrtaceae) and their therapeutic potential. Issue 6 (12th April 2016) - Ravichandran, Subramaniyam; Paluri, Veeranna; Kumar, Gaurav; Loganathan, Karthik; Kokati Venkata, Bhaskara Rao
Abstract : This study describes a novel biological route for the biosynthesis of silver oxide nanoparticles utilising the aqueous extract of Callistemon lanceolatus D.C. leaves. Formation of silver oxide nanoparticles was confirmed by UV–visible spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscope–energy dispersive X-ray spectroscopy and X-ray diffraction spectroscopy analysis. The biologically synthesised silver oxide nanoparticles were found to be 3–30 nm in size with spherical and hexagonal shape by high-resolution transmission electron microscope analysis. Furthermore, the biogenic silver oxide nanoparticles demonstrated significant ( p  < 0.05) dose-dependent antioxidant activity in various in vitro antioxidant methods. These particles also exhibited significant ( p  < 0.05) dose-dependent and time-dependent cytotoxic activity towards brine shrimp nauplii. Moreover, the reported method is a simple, cost-effective and eco-friendly approach for the synthesis of silver oxide nanoparticles with useful pharmacological properties.